PENGARUH PENGALAMAN AUDIT, BEBAN KERJA, DAN INDEPENDENSI TERHADAP KEMAMPUAN AUDITOR DALAM MENDETEKSI KECURANGAN - Muhammad Al Kahfi, - (2019)
The purpose of this study wa to examine the effect of audit experience, workload and independece on the auditor's ability to detect fraud. Population in this research is Public Accounting Firm in Jakarta Area. Sampling was conducted using cluster sampling method at Public Accounting Firm in Jakarta Province. Which produced 53 samples of auditors. Data analysis used in this research is multiple linier regresion with 5% siginificant level. The result on this research show that (1) Audit Experience has no significant effect on the auditor's ability to detect fraud, (2) workload has no significant effect on the auditor's ability to the detect fraud, and (3) independence has signifiant effect on the auditor's abilitty to detect fraud.